1990
DOI: 10.1063/1.859367
|View full text |Cite
|
Sign up to set email alerts
|

Two-component model of strong Langmuir turbulence: Scalings, spectra, and statistics of Langmuir waves

Abstract: A two-component model of strong Langmuir turbulence is developed, in which intense coherent Langmuir wave packets nucleate from and collapse amid a sea of low-level background waves. Power balance between these two components determines the overall scalings of energy density and power dissipation in the turbulence, and of the rate of formation, number density, volume fraction, and characteristic nucleation time of collapsing wave packets. Recent insights into the structure and evolution of collapsing wave pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 28 publications
9
97
2
Order By: Relevance
“…27 On large scales, multiple collapses can occur concurrently, with new wave packets forming elsewhere, mostly at the sites of previous collapses, each surrounded by lower level incoherent waves. 27,39 This is termed strong turbulence, and leads to nonuniform waves, qualitatively similar to those in space plasmas. An example of 2D strong turbulence is seen in Fig.…”
Section: Strong Turbulence Clumping Mechanismsmentioning
confidence: 94%
See 1 more Smart Citation
“…27 On large scales, multiple collapses can occur concurrently, with new wave packets forming elsewhere, mostly at the sites of previous collapses, each surrounded by lower level incoherent waves. 27,39 This is termed strong turbulence, and leads to nonuniform waves, qualitatively similar to those in space plasmas. An example of 2D strong turbulence is seen in Fig.…”
Section: Strong Turbulence Clumping Mechanismsmentioning
confidence: 94%
“…4. 27,39 Power-law distributions of field strength are expected in strong turbulence, with P(E)ϰE Ϫ5 at E rms ӶEՇE t and P(E)ϰexp(ϪE 2 /E t 2 ) at E t ՇE, 27,39,40 where E t is a characteristic field at the end of collapse. Power-law field statistics are also found when averaged over a single collapse.…”
Section: Strong Turbulence Clumping Mechanismsmentioning
confidence: 98%
“…The strong turbulence theory ignores the wave-particle effect, and is a macroscopic theory. Even though Zakharov's strong turbulence theory continues to be investigated by many researchers (see the reviews by Goldman 1984 andRobinson 1997), the theory remains controversial to this date, and various numerical simulations and experiments to confirm the theory are inconclusive (Robinson and Newman 1990;Vyacheslavov et al 2002;Erofeev 2002). …”
Section: A Brief History Of Langmuir Turbulencementioning
confidence: 99%
“…Figure 5 is also inconsistent with the strong Langmuir turbulence process of wave collapse saturating the wave growth, since this process should produce a power-law tail at high E in the P (log E) distribution (Robinson & Newman 1990). Despite early enthusiasm (Papadopoulos, Goldstein & Smith 1974;Smith, Goldstein & Papadopoulos 1979;Thejappa et al 1993), detailed tests of collapse theory against the observed Langmuir waves provide multiple strong arguments against collapse occurring frequently or playing a significant role in type III bursts (Robinson, Cairns & Gurnett 1993;Cairns & Robinson 1995b, 1998Robinson 1997).…”
Section: Type III Solar Radio Burstsmentioning
confidence: 90%